1996
DOI: 10.1017/s0022215100134826
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of partial inferior turbinectomy and cryosurgery for hypertrophic inferior turbinates

Abstract: A variety of surgical procedures are performed for treatment of hypertrophic inferior turbinates, but there is no completely effective therapy. We evaluated subjectively and objectively 52 patients who underwent one of two procedures: partial inferior turbinectomy (PIT) or cryosurgery of the inferior turbinates (CS). The results of PIT showed good functional results in 77 per cent of cases for long-term effectiveness. The results of CS showed that effectiveness was reduced from a 62 per cent success rate after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 15 publications
1
49
0
1
Order By: Relevance
“…PIT was found to be effective in reducing nasal obstruction, nasal discharge, itching & headache in all 30 patients as shown in Table 6 and 7 similar to other studies by Rakover and Rosen. 10 There were 5 cases with recurrence of nasal obstruction from no symptom to mild symptom at 6months in SMD group while no cases of recurrence was observed in the PIT group at 6 months indicating better effectiveness on long term similar to the results showed by Smithachandra et al in their study of 132 patients. 11 All the surgical methods aim mainly in reducing the size of turbinate to relieve nasal obstruction.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…PIT was found to be effective in reducing nasal obstruction, nasal discharge, itching & headache in all 30 patients as shown in Table 6 and 7 similar to other studies by Rakover and Rosen. 10 There were 5 cases with recurrence of nasal obstruction from no symptom to mild symptom at 6months in SMD group while no cases of recurrence was observed in the PIT group at 6 months indicating better effectiveness on long term similar to the results showed by Smithachandra et al in their study of 132 patients. 11 All the surgical methods aim mainly in reducing the size of turbinate to relieve nasal obstruction.…”
Section: Discussionsupporting
confidence: 81%
“…12 Our study had postoperative complications comparable to the study by Rakover and Rosen who had post op bleeding in 12% patients and adhesions in 4% of patients with PIT. 10 Elwany and Harrison also observed post op bleeding in 5% patients & high incidence of postoperative discomfort and headache. 13 A study by Gomma et al showed SMD to be better than PSIT regarding nasal pain and intra-nasal crustations after two weeks, but both techniques were equally effective in improving of nasal obstruction and degree of tissue healing.…”
Section: Discussionmentioning
confidence: 91%
“…Mucosa fail to shrink with nasal decongestants and corticosteroid drops, so the treatment of choice is surgery. Surgical options are electrocautery of inferior turbinates, 2 Submucosal Diathermy (SMD), 3 cryosurgical reduction, 4 Laser surgery, 5 radiofrequency tissue ablation, 6,7 partial inferior turbinectomy (PIT), 8 Inferior Turbinate Bone Resection (ITBR), 9 etc.…”
Section: Physiology Of Nosementioning
confidence: 99%
“…Hemostasis is achieved by nasal packing with neosporin coated gauze pack, which is left for 24-48 hours. 9,25 All patients received antibiotics for 5 days. Nasal packs were removed on 2 nd postop day.…”
Section: Slmentioning
confidence: 99%